New product design for military aviation maintenance activities through quality function deployment (QFD) - Altuntas, Serkan; Dereli, Turkay; Ozsalap, Cengiz (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2019)
In this study, an existing equipment which was already developed by using theory of inventive problem solving (TRIZ) for use in the maintenance operations of the F-16 fighter aircraft, is redesigned through Quality Function Deployment (QFD). Redesign is performed based on the user needs. The equipment is currently used in the maintenance operations of F-16 fighting falcon by Turkish Armed Forces. It has been assessed that the equipment can be improved in terms of user opinions due to the commencement of new use. Therefore, QFD application is performed to reflect the customer'needs during new product development process. The customer requirements are determined from the data obtained through the interview with the quality team created for this study. Based on customer requirements, suggestions are provided for redesign the equipment. There are two important contributions of the current study to literature. First, an equipment, which was already introduced in the literature is redesigned in the current study and an alternative new product is proposed. Second, a real life case study is conducted to show a full illustrative example of Quality Function Deployment (QFD) in defence industry and for systematic product development using QFD. Efficiency and effectiveness in maintenance operations in the military aviation sector can be improved by taking into account the suggestions provided in this study.
Keywords: Defence industry; military aviation sector; Quality Function Deployment; new product design; new product development; AIRCRAFT MAINTENANCE; FUZZY QFD; METHODOLOGY; INTEGRATION; SELECTION; INDUSTRY; REPAIR; FLIGHT; COSTS; MODEL; Engineering